uPAR and cFn as candidate protein biomarkers for identifying low response to rtPA in acute ischemic stroke - Yilin Wang; Yuyou Huang; Fangfang Li; Ziping Han; Zhenhong Yang; Liyuan Zhong; Lingzhi Li; Haiping Zhao; Junfen Fan; Yangmin Zheng; Cesario Borlongan; Yumin Luo (European Journal of Medical Research)
Abstract Background Recombinant tissue plasminogen activator (rtPA) remains the main therapeutic for acute ischemic stroke (AIS). In clinical practice, the patients with AIS presenting low response to rtPA is commonly observed. Cognizant that the endothelial cell function is impaired in AIS, this study explored the endothelial cell-associated proteins as biomarkers that may identify low response to rtPA in AIS. Methods Spearman’s correlation test was performed to assess the relationship between urokinase-type plasminogen activator receptor (uPAR)/cellular fibronectin (cFn) and AIS outcomes. We defined “low response to rtPA” as the patients did not present a lower National Institute of Health Stroke Scale (NIHSS) than at admission and still suffered from poor outcome (modified Rankin Scale > 2) with rtPA use. Logistic regression analysis was used to assess the contribution of uPAR/cFn in identifying low response to rtPA in AIS. The relationship between uPAR/cFn and rtPA was further probed in Sprague–Dawley rats with experimental stroke induced by middle cerebral artery occlusion. Results Both uPAR (P < 0.001) and cFn (P = 0.001) positively correlated with AIS favorable outcomes. uPAR (AUC = 68.2%, P = 0.007) and cFn (AUC = 71.3%, P = 0.002) can identify low response to rtPA. Additionally, uPAR (P = 0.015) and cFn (P = 0.004) were independent variables that predicted low response to rtPA. At 24 h and 72 h ischemic/reperfusion, rtPA tended to decrease cFn and uPAR plasma levels. Conclusions Our study suggests that uPAR and cFn may serve as the candidate markers for identifying low response to rtPA in AIS. Patients with a low plasma level of cFn or uPAR may present low response to rtPA and still suffer from a poor outcome with rtPA.